Jumping and leaping estimations using optic flow - Lin, Lisa P. Y.; Linkenauger, Sally A.; Justus Liebig University Giessen (My University, 2024)
Optic flow provides information on movement direction and speed during locomotion. Changing the relationship between optic flow and walking speed via training has been shown to influence subsequent distance and hill steepness estimations. Previous research has shown that experience with slow optic flow at a given walking speed was associated with increased effort and distance overestimation in comparison to experiencing with fast optic flow at the same walking speed. Here, we investigated whether exposure to different optic flow speeds relative to gait influences perceptions of leaping and jumping ability. Participants estimated their maximum leaping and jumping ability after exposure to either fast or moderate optic flow at the same walking speed. Those calibrated to fast optic flow estimated farther leaping and jumping abilities than those calibrated to moderate optic flow. Findings suggest that recalibration between optic flow and walking speed may specify an action boundary when calibrated or scaled to actions such as leaping, and possibly, the manipulation of optic flow speed has resulted in a change in the associated anticipated effort for walking a prescribed distance, which in turn influence one’s perceived action capabilities for jumping and leaping.
Keywords: ddc:150